2019
DOI: 10.1111/jdv.16071
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of circulating subpopulations of T‐regulatory cells in patients with hidradenitis suppurativa

Abstract: Background Decreased number of T‐regulatory cells (Tregs) and/or their loss of function potentially lead to uncontrolled immune‐mediated inflammatory responses. There are only few data available on Tregs in hidradenitis suppurativa (HS) – a disease in which it has been suggested that host immune factors and an overactive immune system of the follicular epithelium play a pathogenetic role. Objectives To analyse frequencies of Tregs subpopulations in blood of HS patients in comparison with a healthy control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
(95 reference statements)
0
7
0
1
Order By: Relevance
“…MicroRNAs (miRNAs) are small molecules that negatively regulate gene expression and serve as effective biomarkers due to their abundance, cell‐type and disease‐stage specificity, and stability in clinical samples. Prior studies showed that miRNA processing factors (including Drosha and Dicer), as well as components of the RISC complex (AGO proteins), are distinctly and progressively downregulated from normal, perilesional, to lesional HS skin. The presence of many inflammatory miRNAs in lesional HS suggests a typical inflammatory response obscuring keratinocyte contribution .…”
Section: Scientific Session 3: Pathophysiology Of Hidradenitis Suppurmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small molecules that negatively regulate gene expression and serve as effective biomarkers due to their abundance, cell‐type and disease‐stage specificity, and stability in clinical samples. Prior studies showed that miRNA processing factors (including Drosha and Dicer), as well as components of the RISC complex (AGO proteins), are distinctly and progressively downregulated from normal, perilesional, to lesional HS skin. The presence of many inflammatory miRNAs in lesional HS suggests a typical inflammatory response obscuring keratinocyte contribution .…”
Section: Scientific Session 3: Pathophysiology Of Hidradenitis Suppurmentioning
confidence: 99%
“…48 An interesting biomarker that showed a significant response to adalimumab in super-responders was MIP-3b, a homing chemoattractant that promotes T cells and dendritic cells to areas of lymphoid tissue where T-cell priming occurs. 40,41 Recent studies have shown that T effector and Treg cells are dysregulated in the circulation and HS lesional skin, 49 and the T effector/Treg axis was corrected in the circulation and lesional skin of patients with HS after receiving adalimumab. 50 A reduction in the inflammatory factors IL-8 and MIP-3b suggests that the inhibition of pathogenic effector T cells via TNF blockade may be associated with an improvement in immune dysregulation in HS, also providing additional insight into the mechanism of action of adalimumab in HS.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have focused on the role of immune dysregulation with complement abnormalities [ 31 , 32 ]. Recently, innate immunity, auto-inflammatory mechanisms, and distribution of certain T-cell lymphocyte subpopulations have been shown to influence the pathophysiology of HS [ 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%